ANALISIS POSITIONING DAN SEGMENTASI SURAT KABAR : Suatu Studi tentang Pemetaan persepsi konsumen di kotamadya Malang - Ratnawati, Afifah (JURNAL BISNIS STRATEGI, 2001)
This study analyzed consumer perception of daily newspapers in Malang Municipality. This research was conducted based on the fact that in the reformation era, there are a lot of newspapers being published in Indonesia, indicating that the competition in this business field is tight.The objective of this research was to find out the perceived relative image of the nespapers in Malang Municipality, in order to establish the position of each newspaper relative to other competitors from the consumer point of view. The research aimed at identifying the most preferred nespaper based on the attributes used in perceiving nespapers.The research was conducted from November 1998 through January 1999. Purposive sampling and non proporsional random sampling were employed to determine the samples. Purposive sampling was employed to determine target population and the choose the consumer groups of the newspaper studied. Non proportional random sampling was employed to take respondents from every group of newspapers. Their were 105 respondents these were subscribers of Jawa Pos, Surya, Kompas, Republika, Malang Pos, Surabaya Pos and Memorandum.Data analysis used the descriptive model and the graphic as well. From the descriptive approach, it was found that in comparing newspapers, most respondent used the following attributes: 1) national news, 2) objectivity of the news, 3) political news, 4) sosiocultural news, 5) economics and business news, 6) international news, 7) regional news, 8) articles and analysis, 9) sports news, 10) physical appearance, and 11) newspaper distribution.The grafic approach used multi-dementional scaling analysis, cluster analysis, and vector analysis. Graphics approach showed that the position of the newspapers in Malang Municipality on the perceptual map is as follows. Jawa Pos is perceived to be simillar with Surya, while Kompas is also perceived to be simillar with Republika. Memorandum is perceived to be different from Jawa Pos, Kompas, Surya, Surabay Pos, Malang Pos, Kompas, Republika, and Bisnis Indonesia.The grouping of newspapers based on consumer perception of the simillarity of newspapers, shows that there are three segments of newspapers, namely: segments I comprising of Jawa Pos, Surya, surabaya Pos, and Malang Pos, segment II comprising of Kompas, Republika and Bisnis Indonesia and segment III comprising of Memorandum.Another result of the research shows that, if viewed from the vector representation, Jawa Pos, Surya, and Surabaya Pos arliked most by consumers especially on the attributes of regional news, distribution as well as national and sports news. Kompas and Republika are preferred by consumers because of their atrributes of physical performance, article and analysis, economic and business news, national news, political news objectivity, international news, socio cultural news as well as sports. Bisnis Indonesia is preferred because of economic and business news, while Malang Pos and Memorandum are preferred because of regional news presented.